Variations in the Spatial Distribution of Areas of Economic Growth and Stagnation in Poland: Determinants and Consequences - Churski, Paweł (Quaestiones Geographicae, 2014)
The results presented here come from one of the stages of a research conducted under the project Socio-economic development and the formation of areas of economic growth and stagnation, funded by the National Science Centre (N N306 791940). The project is implemented by a team of staff members of the Department of Regional Analysis of the Institute of Socio-Economic Geography and Spatial Management, Adam Mickiewicz University in Poznań, headed by the present author.